Serum irisin levels as a potential marker for diagnosis of gestational diabetes mellitus - AL-Ghazali, Majid Jawad; Ali, Hanaa Addai; AL-Rufaie, Mohauman Mohammad (Acta Biomedica Atenei Parmensis, 2020)
Objectives: The aim of this study was to compare serum irisin, trace elements (Zn, Cu, Mg) levels between the group of pregnant women with gestational diabetes mellitus (GDM) and healthy pregnant group. Material and methods: Sixty pregnant women with GDM and 30 healthy pregnant women. The two groups were matched for maternal age, gestational age. Maternal serum irisin levels were measured by enzyme-linked immunosorbent assay kit at 24-28 weeks of gestation. An association between maternal serum irisin levels and clinical and biochemical parameters was evaluated. Body mass index, serum levels of glucose, OGTT, insulin, HbA1C, HOMA IR, HOMAβ, Hb%, and irisin were investigated and analyzed in the study group and controls. Results: Pregnant women with GDM had significantly higher fasting blood glucose FBG (p = 0.004), first-houEr OGTT glucose (p = 0.001), second-hour OGTT glucose (p = 0.001), fasting insulin FI (p = 0.001) levels, HOMA IR (p = 0.001), HOMAβ (p = 0.001), HbA1C(p = 0.001), Hb% (p = 0.017), as compared to controls. serum irisin levels were significantly lower (p =0.001) in women subsequently developed GDM (mean ± SD =71.65±8.03) than healthy pregnant controls (mean ± SD 136.54±22.56). Correlation analysis between irisin levels and anthropometric and biochemical parameters in patients with gestational diabetes revealed that none of the investigated parameters correlated with serum irisin level. Conclusions: The present results suggest that serum irisin levels might presented as a novel marker for GDM, with decreased levels of irisin being symptomatic of GDM.